A Role of TDIF Peptide Signaling in Vascular Cell Differentiation is Conserved Among Euphyllophytes - Hirakawa, Yuki; Bowman, John L. (Frontiers in Plant Science, 2015)
Peptide signals mediate a variety of cell-to-cell communication crucial for plant growth and development. During Arabidopsis thaliana vascular development, a CLE (CLAVATA3/EMBRYO SURROUNDING REGION-related) family peptide hormone, TDIF (tracheary element differentiation inhibitory factor), regulates procambial cell fate by its inhibitory activity on xylem differentiation. To address if this activity is conserved among vascular plants, we performed comparative analyses of TDIF signaling in non-flowering vascular plants (gymnosperms, monilophytes and lycophytes). We identified orthologs of TDIF/CLE as well as its receptor TDR/PXY (TDIF RECEPTOR/PHLOEM INTERCALATED WITH XYLEM) in Ginkgo biloba, Adiantum aethiopicum and Selaginella kraussiana by RACE-PCR. The predicted TDIF peptide sequences in seed plants and monilophytes were identical to that of A. thaliana TDIF. We examined the effects of exogenous CLE peptide-motif sequences of TDIF in these species. We found that liquid culturing of dissected leaves or shoots was useful for examining TDIF activity during vascular development. TDIF treatment suppressed xylem/tracheary element differentiation of procambial cells in G. bioloba and A. aethiopicum leaves. In contrast, neither TDIF nor putative endogenous TDIF inhibited xylem differentiation in developing shoots and rhizophores of S. kraussiana. These data suggest that activity of TDIF in vascular development is conserved among extant euphyllophytes. In addition to the conserved function, via liquid culturing of its bulbils, we found a novel inhibitory activity on root growth in the monilophyte Asplenium x lucrosum suggesting lineage-specific co-option of peptide signaling occurred during the evolution of vascular plant organs.